2019
DOI: 10.3389/fphar.2019.00557
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Target Network Reveals Potential for Cancer Combination Therapies

Abstract: A body of research demonstrates examples of in vitro and in vivo synergy between natural products and anti-neoplastic drugs for some cancers. However, the underlying biological mechanisms are still elusive. To better understand biological entities targeted by natural products and therefore provide rational evidence for future novel combination therapies for cancer treatment, we assess the targetable space of natural products using public domain compound-target info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 65 publications
(96 reference statements)
0
36
0
Order By: Relevance
“…A recent study revealed the potential synergistic effect of increasing pathways targeting coverage in combinatorial regimens consisting of phytochemical compounds and chemotherapy [56]. Phytochemical compounds also have the potential to alleviate toxicity induced by chemotherapy, further justifying their usage along with the traditional treatment modalities [55].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed the potential synergistic effect of increasing pathways targeting coverage in combinatorial regimens consisting of phytochemical compounds and chemotherapy [56]. Phytochemical compounds also have the potential to alleviate toxicity induced by chemotherapy, further justifying their usage along with the traditional treatment modalities [55].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a slight effect was observed with 50 and 100 µM. As cancer is a multifactorial disease, it requires treatment with compounds able to target multiple intracellular molecules [33,34]. Traditional medicines and natural products are used as direct sources of natural agents that harbor multiple therapeutic effects [24,35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combined treatment of A. graveolens fraction, sensitized cancer cells in vitro and cisplatin/etoposide/doxorubicin through the induction of ROS and caspase-3-dependent apoptosis 44 . The mode of action of a combination of drugs is different than that of the same drugs acting individually; hence isolating a single component may lose its effectiveness 79,80 .The versatility of a natural product target network, for example, suggests that plant extracts can serve as good candidates for cancer combination therapies 81 . Schweinf.…”
Section: Combined Therapy May Have a Better Outcome Than Single Treatmentioning
confidence: 99%